Specialized insectivores drive differences in avian community composition between primary and secondary forest in Central Africa - Barrie, Eleanor M.; Krochuk, Billi A.; Jarrett, Crinan; Ferreira, Diogo F.; Rodrigues, Patricia F.; Mufumu, Susana Lin; Malanza, Silvestre Esteban; Akele, Agustin Ebana Nsue; Alene, Cayetano Ebana Ebana; Brzeski, Kristin E.; Cooper, Jacob. C.; Wolfe, Jared D.; et al. (Frontiers in Conservation Science, 2025)
The human population of sub-Saharan Africa is projected to triple by 2100, drastically increasing anthropogenic pressure on biodiversity. When rainforest is disturbed by anthropogenic drivers, species respond heterogeneously; these patterns have rarely been quantified for Congo rainforest fauna. Our objective was to understand how community composition changed with human disturbance—with particular interest in the guilds and species that indicate primary rainforest. At a long-term bird banding site on mainland Equatorial Guinea, we captured over 3200 birds across 6 field seasons in selectively logged secondary forest and in largely undisturbed primary forest. Our multivariate ordination indicated a significant split between primary and secondary forest communities. We caught 47% fewer birds in secondary forest overall, with Dorylus ant-followers, mixed-species flockers and terrestrial insectivores showing at least two-fold reductions. We identified 12 species that were characteristic of primary forest. Of those, 10 were strict insectivores: terrestrial insectivores (Sheppardia cyornithopsis, Illadopsis cleaveri, I. fulvescens/rufipennis), mixed-flockers (Phyllastrephus icterinus/xavieri, Elminia nigromitrata, Terpsiphone rufiventer, Pardipicus nivosus, Deleornis fraseri), ant-followers (Alethe castanea, Chamaetylas poliocephala), White-bellied Kingfisher (Corythornis leucogaster), and Blue-headed Wood Dove (Turtur brehmeri). Only the kingfisher Ispidina lecontei was captured more in secondary forest. This contributes to a growing body of Pantropical literature suggesting that insectivores living on or near the forest floor are vulnerable to rainforest degradation. Notably, few species disappeared entirely in secondary forest (unlike patterns seen in the Neotropics); rather, capture rates of 12 of 30 species (40%) were significantly reduced relative to primary forest. By understanding disturbance-sensitive guilds and species, we might identify the proximate mechanisms responsible for the loss of Afrotropical birds, thus helping to manage communities as forest disturbance continues.